Vested interests: the incorporation of immigrants into the informal economy. - Ambrosini, Maurizio (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
Immigrants’ participation in the underground economy in Italy as well as abroad, is very often evoked and denounced in tones of alarm but its constitutive processes, its relevant processes or its connections with the economy and the society in which it is situated are very seldom studied in depth. Our researches have shown the existence of a labyrinth of institutional links, business interests and ways of self-organization of the immigrant offer, which have opened up a valid space for the informal integration of the immigrant workers.